STRATEGI PENGEMBANGAN AGROWISATA DI KOTA SEMARANG - Tri Widayati; Nugroho SBM (Jurnal Riptek, 2018)
The purpose of this research is to formulate the strategic plan ofagrotourism development in Semarang City. Its development is based on the uniqueness and local pre-eminent sectors such as agriculture,livestock, services, etc. It is conducted through a participatoryapproach. The approach method uses the qualitative method. The resultsfound that there are several policies that must be taken by theSemarang’s Government for agrotourism’s development. The policy involves the management of assets, objects, and tourist destinations, and management of existing facilities or agrotourism local amenities.In the development of the agrotourism, the city Government mustinvolve the community, NGOs, and private.